Mechanisms for managing ambidexterity: a review and research agenda - Turner, N; Swart, J; Maylor, H (Wiley, 2013)
Ambidexterity is of central importance to the competitive advantage of the firm, yet to date there is limited understanding of how it is managed. The theorization of ambidexterity is inadequate for complex, practical realities and, in turn, this hinders the way in which it can aid the management of ambidexterity in practice. This paper asks: What are the mechanisms for achieving ambidexterity? The authors use a systematic review to develop a research framework which integrates intellectual capital resources (organizational, social and human capital) across various levels of analysis (organization, group and individual). This review extends understanding of the generic mechanisms (i.e. temporal, structural and contextual ambidexterity) that dominate the literature. This allows for a more fine‐grained understanding of how ambidexterity is achieved and enables avenues for further research to be identified.